Paediatric appendiceal neuroendocrine tumours: a review of 33 cases from a single center. Issue 4 (18th October 2021) - Yalçın, Bilgehan; Karnak, İbrahim and Orhan, Diclehan and Oğuz, Berna and Aydın, Burça and Kurucu, Nilgün and Varan, Ali and Kutluk, Tezer
Abstract: Background: Appendiceal neurendocrine tumours (NETs) are rare neoplasms and diagnosis is commonly incidental following appendectomy. We aimed to review our experience with appendiceal NETs. Methods: Records of children with appendiceal NETs were reviewed and data concerning demographic characteristics, clinical findings, surgical procedures, histopathological findings, management and outcomes were recorded. Results: Between 1985 and 2021, 33 cases with appendiceal NETs (median age 11.8 years, range 7.8–16; male/female = 10/23) were identified. All but one patients presented with abdominal pain, six had vomiting, four had fever and they underwent appendectomies with presumed diagnosis of acute appendicitis. Abscess drainage and appendectomy was performed in a 16‐year‐old girl for suspected right ovarian mass, and tumour was positive in the omentum. Histopathological diagnosis was classical carcinoid tumour (NET) in all cases. Median tumour size was 0.9 cm ( n = 26, range, 0.1–3.5 cm); tumours were ≤1 cm in 19 cases, 2 cm in one, 3.5 cm in another case. Tumours were located in the tip ( n = 11), body ( n = 6) and base of appendix ( n = 1) (in others data unavailable). In 28 patients with data, tumour extended to submucosa in five, to tunica muscularis in seven, to subserosa in six, to serosa in six, to mesoappendix in three, to periappendiceal fat in one. Three cases were lost to follow‐up, 31 cases were alive (median follow‐up 53 months). Conclusions: Paediatric appendiceal NETs do not behave aggressively and appendectomy alone is sufficient for tumours ≤2 cm regardless of local invasion. The need for further extensive surgery in tumours >2 cm also remains controversial. Abstract : Paediatric appendiceal neurendocrine tumours are quite rare. These tumours do not behave aggressively in children and appendectomy alone is sufficient for most tumours regardless of local invasion. The need for further extensive surgery in tumours >2 cm also remains controversial.